Portrait 1111 : Fourth Annual Exhibition of the Soros Center for Contemporary Arts Skopje, Macedonia. (Skopje : SCCA (Soros Center for Contemporary Arts), 1998)
Abadzieva, Sonja ; Avramovska, Elizabeta ; Budzevac, Dejan ; Maznevski, Antoni ; Plavevska, Marika Bocvarova ; Adzievski, Tome ; Dimitrovski, Valentino ; Serafimovska, Nada Prlja ; Miljanovska, Kristina ; Dimanovski, Valentin ; Jarcevska, Ivana ; Drakailskia, Dusan ; Penv, Hristijan ; Kondev, Aleksandar ; Pisarev, Nikola ; Stojanovic-Suki, Miroslav ; Sarkanjac, Branislav ; Stankovski, Aleksandar ; Dzeparoski, Ivan ; Dimitrova, Iskra
Fourth Annual Exhibition of the Soros Center for Contemporary Arts Skopje, Macedonia, 8 - 18 July 1998
Engels & Macedonisch
boek